Decide Madrid: a case study on e-Participation - and Pina, Vicente; Torres, Lourdes; Royo, Sonia; García-Rayado, Jaime (2019)
This paper analyses the award-winning e-participation initiative of the city council of Madrid, Decide Madrid, to discover the critical success factors at contextual, organizational and individual level. This analysis is carried out with desk research and semi-structured interviews. Results show that the most relevant success factors are the socio-economic context, the commitment of the city council, the method used to recruit the workers and the knowledge of senior managers about citizen participation and ICTs. However, the lack of transparency and poor functioning of some of its participation activities are negatively affecting its performance.